Terpaan Postingan Voucher E-Commerce pada Akun X @discountfess terhadap Pembelian Impulsif Produk Kecantikan Followers - Alika, Vina; Dharta, Firdaus Yuni; Arindawati, Weni Adityasning (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Information that often attracts users of social media account X is information related to promotions. Information about promotions shared by the @discountfess autobase account can lead to followers' impulse buying behavior on beauty products. This study uses the S-O-R theory (Stimulus-Organism-Response). The purpose of this study is to determine whether there is an effect of exposure to e-commerce voucher information content from account X @discountfess on impulse purchases of beauty products on followers. The population of this study were followers of the X @discountfess account with sampling using purposive sampling. This study obtained 400 respondents from the questionnaire. The data analysis methods used in this study are descriptive statistical tests, classical assumption tests, multiple linear regression tests, t tests, F tests, and coefficient of determination ) tests. This study shows several results, namely the absence of the influence of frequency and duration but the influence of attention on exposure to e-commerce voucher posts on impulsive purchases of beauty products, and the influence of exposure to e-commerce voucher posts on impulsive purchases of beauty products on followers.